How Website's Atmosphere affect Consumer Behavior: a new model based on the stimulus- organism-response (SOR) framework - Nanang Fitriana Kurniawan; Eko Madiasto; Primidya KM Soesilo (Journal of Business, Management, & Accounting, 2021)
In these decades, there have been many researchers discussing this field of study, but currently little is known about the factors designed and configured using atmospheric websites that optimize the experience for consumers (flow experiences) in increasing the desire to conduct transactions (Purchase Intention) on the website. Based on the subject matter that has been discussed previously, then in an effort to increase competitive web. So it is necessary to increase the role of web interface design and the delivery of atmospheric websites that are controlled in facilitating visitors. The S-O-R model consists of a stimulus that functions as an independent variable, organism as a mediator variable and the response functions as a dependent variable. Limitations in this study, that the respondents were selected based on the criteria of the researcher, as well as limitations in obtaining respondents to fill their perceptions of the use of online travel services and lack of documentation of the characteristics of the respondents. all variables have a significant influence on experience. Thus, it is important for future research to use several other behavioral factors that can influence website usage in creating consumer intentions and satisfaction. It is also recommended to use actual tourist samples